DETERIORO COGNITIVO Y ÁREA EMOCIONAL EN LOS ADULTOS MAYORES DE LA ASOCIACIÓN DE JUBILADOS Y PENSIONISTAS " MANUELA CAÑIZARES" DEL CANTÓN BABAHOYO - NAVAS JIMENEZ DAYANNA ALEXANDRA (2024)
Cognitive decline is a natural process associated with aging, in which significant changes occur, both in the ability to process information, remember and make decisions. This wear and tear can affect different cognitive areas, such as memory, attention, language and skills. As cognitive decline progresses, it can also have an impact on the emotional area of older people. Since, it can affect the mental abilities to manage their emotions, express their feelings and relate to society. The impact on the emotional area can be difficult for both the person experiencing cognitive impairment and their loved ones or people around them. It can lead to feelings of frustration, sadness, confusion, and even isolation. Thus, with the aforementioned, interest arises in identifying cognitive deterioration and how it affects the emotional area of older adults, so, first of all, the basic and higher cognitive processes were evaluated with the help of the mini mental test. In addition, we also worked with a questionnaire that included questions about the emotional area, so that the influence of emotions on the mental state of older adults is important. These measurement instruments managed to collect data that were applied to 80 older adults who attend the "Manuela Cañizares" association of retirees and pensioners. This study was carried out through descriptive research, in which it is concluded that cognitive deterioration not only affects the information processing capacity, but also It can also have an impact on the emotional area of older adults.